Synthesis and Photocatalytic Activity of One-Dimensional CdS@TiO2 Core-Shell Heterostructures - Wei, Hongwei; Wang, Le; Li, Zhipeng; Ni, Shouqing; Zhao, Quanqin (Nano-Micro Letters, 2011)
One-dimensional CdS@TiO2 core-shell heterostructures were fabricated via the hydrolysis of tetrabutyl titanate (TBT) on preformed CdS nanowires. The as-prepared products were characterized by X-ray diffraction, transmission electron microscopy, selected area electron diffraction and diffuse reflectance spectroscopy techniques. Results demonstrated that the hydrolysis of TBT had a great influence on the morphology of the coated TiO2 shell, resulting in the formation of TiO2 nanoparticles and nanolayer-modified CdS@TiO2 heterostructures. Degradation of methylene blue using CdS@TiO2 core-shell heterostructures as photocatalysts under visible light irradiation was investigated. Comparative photocatalytic tests showed that the TiO2 nanoparticles-modified heterostructure exhibited a superior activity due to the passivity of photogenerated charge carriers.